(untitled) (LACCEI, 2024)
The objective of the research work is to analyze and design the structure of the recreational and pedagogical area for an educational institution in Peru. For the present investigation it has been proposed to expand an educational institution located in Trujillo - Peru (Pacific fire belt) with seismic risk. Environments designed with the technical standard of design criteria for educational premises of MINEDU and the national building regulations. Regarding the structural issue of the educational environments, we complied with the requirements of the E.030 Seismic Resistant Design Standard, consolidated with the Etabs software. In the seismic analysis, drifts of less than 0.007 were obtained, with a maximum drift of 0.001434 in the X axis and 0.004591 in the Y axis for the steel design, all load combinations established in the E060 standard were taken into account. Regarding the recreational theme, a semi-Olympic pool of 25m long and 12.5m wide with a depth of 1.80m was considered, thus complying with the minimum parameters of the technical standard. When returning to classroom activities after the inclemencies of the pandemic that has been experienced, it is necessary that all private and public educational institutions are evaluated structurally to verify whether they meet the parameters of functionality and safety, and thus, establish the necessary repairs or reinforcements, with the sole purpose of ensuring the lives of children and young people.